Doing Lernbegleitung Hochschullernwerkstätten als Orte der Generationenvermittlung - Gruhn, Annika (Lernen und Studieren in Lernwerkstätten, 2021)
The study "Doing Lernbegleitung. Hochschullernwerkstätten als Orte der Generationenvermittlung" addresses the so-called first phase of teacher training at German universities. Based on an examination of the special features of the research field of university learning workshops, the study explores the question of how teacher trainees are confronted with the pedagogical concepts of individualization as well as open and informal education. It focuses the introduction to a specific professional understanding of teachers as learning companions within the framework of the practical project "Werkstatt für Kinder" of the university learning workshop OASE at the University of Siegen: Thus, the implementation of the conceptual self-understanding in the social practice will be focused on. In order to ethnographically explore learning companionship as a specific bundle of social practices, both the preparation for the "Werkstatt für Kinder" within the student peer group and the social construction of students as learning companions for children will be examined. This approach allows to successively describe typical challenges of both students and children as well as the associated specific fields of tension and conflicts of the pedagogical setting of the university learning workshop from an empirically based perspective. The study is characterized by a very personal approach to the field and thus an involved researcher position, which is used as an analytical tool in the research process. The empirical results are presented according to the unfolding of social practice in the field and then linked to two theoretical frameworks, generational order as well as (pedagogical) spaces and things. Thus, learning companionship is reconstructed as a bundle of specific social practices situated in the OASE university learning workshop, which can be explored and described as the production of generational order embracing the triad of human actors, spaces and things. This theoretical and analytical perspective challenges the normative understanding contrasting "traditional" and "alternative" pedagogic concepts (for example differences between teaching and learning companionship or between children and students) by describing differences as an effect and medium of social practice.